Quality of Sleep among the Patients in High Dependency Unit (Hdu)- A Descriptive Study - Shruti Dabhade,1 Manisha Mistry,2 Dipali Dumbre3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background:Sleep is a vital physiologic process, serious outcomes results due to lack of sleep. The circadianrhythm plays an important role in our biologic function. Various studies have recorded the function ofcircadian rhythm in our body and the various environmental parameters which affect the sleep of the patients.Along with other factors critical illness also contributes to the vulnerability of the patient.The recovery ofthe patients depends on the quality of the sleep. Hence this study assess the quality of sleep among thepatients in HDU.Objective:To assess the quality of sleep among the patients in HDU.Methodology: A NonExperimental Descriptive Research Approach is used. 30 samples who had three days of HDU stay wereselected by using NonProbability Purposive Sampling Technique. Data was congregated using ModifiedPittsburgh sleep Quality Index.In order to establish the reliability of the tool test-retest method was usedand the pearson’s correlation coefficient was found to be 0.98. Result: Majority of them, 50% had agegroup of 41-50 years. 23% had age group of 51-60 years and 13.33% has 31-40 years and above 60 yearsage group. Majority 66.67% were male and few 33.33% were female. Majority 63.33% had three days ofHDU stay whereas 36.67% had 4 days of HDU stay. 33.33% had diagnosis related to cardiovascular, 30%had respiratory related diagnosis, 20% were related to gastrointestinal, 13.34 % were from endocrine andfew 3.33% were from other systems. The quality of sleep reveals that majority 40% of them had poor sleep(score 30-44), 26.66% had average sleep (score 15-29), 20% had good sleep (score 1-14), 13.33% had verygood sleep (score 0)Conclusion: The findings indicate that the questionnaire was effective in assessing thequality of sleep among the patients in HDU. The study also concluded that majority of the patients in HDUhad poor quality of sleep.